Deliberating Foreign Policy: Perceptions and Effects of Citizen Participation in Germany. Issue 4 (2nd October 2021) - Pfeifer, Hanna; Opitz, Christian; Geis, Anna
Abstract : Citizen participation has been a popular format in policy fields like environmental and climate policies for many years. More recently, however, it has extended to issues of foreign policy which has long been considered as a prerogative of the executive in democratic systems. This paper analyses citizen participation in German foreign policy by comparing deliberative-participatory processes implemented by the German Federal Foreign Office (AA) and the Ministry for the Environment, Nature Conservation, and Nuclear Safety (BMU). We draw on recent scholarship in the field of deliberative democracy in order to gain a better understanding how the two ministries understand citizen participation, how they implement these processes, and what effects they have on formal decision-making. Using interviews, participant observation, and document analysis, we investigate two processes of citizen participation in depth. We argue that ministerial understandings of citizen participation determine how they design formats in their respective field. This leads to quite divergent implementations and results of deliberative-participatory formats in the field of foreign policy, depending on whether the AA or the BMU initiates them.